Effectiveness of Pilates Exercise on Disability in Low Back Pain Patients: A Meta-analysis Review Paper - Keyvan Sharifmoradi; Saeed reza Nori monfared (Shiraz University of Medical Sciences, 2020)
Background: The aim of this meta-analysis review study was to examine and summarize the benefits of Pilate's exercises on disability in patients with low back pain (LBP). Methods: Research was conducted from March 2005 to December 2018. Patients with chronic low back pain formed the statistical population of this study. The keywords were Pilates together with low back pain, chronic low back pain, and back pain. The Medline, Embase, Pubmed, Google Scholar, Scopus, and SID databases were searched for relevant literature. Results: Nineteen papers, including 15 high quality and 4 poor quality papers, were assessed. The results showed that Pilates exercises had a significant and high effect size (p =0.000) on disability in comparison with the control group (Hedges g=1.183) as well as a significant (p =0.000) and medium effect size compared with the exercise group (Hedges g=0.526). When the durability of the Pilates exercise effect was assessed in the follow-up period, a significant and low effect size (p =0.017) was found in the Pilates group compared with the control group (Hedges g=0.488). Conclusion Pilates exercises improved the stability of patients with LBP compared to the control group. The effect of Pilates exercises decreased during follow-up after 13 weeks of inactivity. Pilates exercises are more effective than other types of exercise. Equipment Pilates exercises have a greater effect than mat Pilates on disability improvement during the follow-up periods; thus, it is advisable for therapists to use Pilates-based equipment exercises to increase the stability of patients with LBP.